ORGANIZATION OF CAREER GUIDANCE AT THE UNIVERSITY - Valentin S. Skripkin; Nelli A. Tunina (Высшее образование в России)
The article covers the problem of agricultural universitygraduates employment and describesa positive experience ofthe leading Russian agricultural university - the Stavropol State Agricultural University in this sphere. Some important steps are the following: the organization of career guidance according to the specialization, arrangements for students’ working practice, modern material and technical base, meetings with potential employers, cooperationwith the Executive Authorities of the Stavropol region and with former graduates of the University.